Environmental fate of cefquinome: Adsorption and degradation - Qiu, Jicheng; Yang, Yuxin; Kong, Jingyuan; Cao, Yuying; Liu, Yu; Sun, Feifei; Cao, Xingyuan (Frontiers in Environmental Science, 2022)
Cefquinome (CEQ), the fourth generation of cephalosporins, has been widely used in practice for the treatment of bacterial infections due to its broad antimicrobial spectrum, stability, and stronger antibacterial activity. However, the wide use of CEQ can cause an environmental risk via animal excretion. In the current study, the environmental fate of CEQ was investigated. The migration rate of CEQ from soil to the aquatic environment was approximately 60%. The half-life (T1/2) of CEQ degradation in the water ranged from 0.96 to 13.75 d. Our results showed that the temperature, illumination and pH had an effect on the degradation rate, and the rate of CEQ degradation was significantly accelerated under high temperature. CEQ was more stable in acidic environments than in alkaline. E-isomer of CEQ and △3-isomer of CEQ were the major degradation metabolites identified by UPLC-Q Orbitrap MS. The product ion m/z 293.041was the typical fragment ion for E-isomer of cephalosporin, and m/z 201 and m/z 152 were the typical fragment ion for △3-isomer of cephalosporin. The degradation metabolites exhibited lower antibacterial activity, simultaneously, the toxicity of E-isomer of CEQ should pay more attention to.